LOCAL OZONOTERAPIYA'S APPLICATIONS IN TREATMENT OF PATIENTS WITH IT IS LONG NOT HEALING DISEASES OF SOFT FABRICS - I. L. Mikitin; Yu. S. Vinnik; G. E. Karapetyan; N. M. Markelova; M. N. Kuznetsov; A. A. Zakharchenko; А. V. Popov; G. N. Gulikyan; V. A. Arapova (Креативная хирургия и онкология)
In  work  results  of  treatment of  patients are  presented with  is  long  not  healing purulent diseases  of soft  fabrics.  To therapy of the first group  of patients (27) along with traditional treatment carried out bandagings with drawing  the ozonized olive oil. As a result of  research it is revealed  that  application of  a method of  a local ozonoterapy allows to accelerate considerably healing process  to a wound  to reduce  stay terms  on a hospital  bed on the average by 20% with the localized is long not healing processes and for 16% with the unlimited is long not healing processes.